A Mindfulness Curriculum: High School Students’ Experiences of Yoga in a Nova Scotia School (LEARNing Landscapes, 2017)
This article reports on results from a narrative inquiry into the experiences of four students who completed an elective yoga course as part of their high school program in the province of Nova Scotia, Canada. Semi-structured interviews were conducted to understand the participants' stories of their yoga experiences. Overall, students were able to express and give examples of how yoga made them feel stronger, happier, kinder, and more self-confident. We suggest that Yoga 11 is a mindfulness curriculum, inherently. This research might be of particular interest to others similarly engaged in research related to mental health and mindfulness in education.
Keywords: well-being; mental health; yoga; mindfulness; high school; narrative; interview; curriculum